ANALISIS PEMANFAATAN SARANA DAN PRASARANA OLAHRAGA DI LINGKUNGAN SEKOLAH DALAM MENDUKUNG AKTIVITAS FISIK SISWA - Andi Sri Rafiqa Hayu; Muhammad Iksar; Riska Jaya; Supirman Rais; Muhammad Haerul (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The utilization of sports facilities and infrastructure within schools plays a crucial role in supporting student physical activity and facilitating the success of the Physical Education, Sports, and Health (PJOK) curriculum. Adequate sports facilities and their optimal use can boost student participation in various physical activities, both during and outside of scheduled class hours. This study aims to analyze how school sports facilities and infrastructure are utilized to support student physical activity. A quantitative descriptive research approach was employed, utilizing data collection methods such as observation, questionnaires, and documentation. The study subjects included students, physical education teachers, and school personnel involved in facility management. The collected data were analyzed using descriptive percentage analysis to determine the extent to which the available sports facilities and infrastructure were utilized. The results indicate that the majority of school sports facilities and infrastructure are effectively utilized for both instructional and extracurricular activities. However, certain challenges remain, such as a limited number of facilities, poor maintenance of equipment, and suboptimal scheduling. Nevertheless, effective utilization of sports facilities has been shown to positively impact student physical activity levels, exercise motivation, and participation in school sports activities.Based on the findings, it can be concluded that the effective and sustainable use of sports facilities and infrastructure can optimally support student physical activity. Therefore, school authorities need to focus on improving the quality, quantity, and management of sports facilities to foster a healthy, active, and productive learning environment.